1995
DOI: 10.1007/bf02191873
|View full text |Cite
|
Sign up to set email alerts
|

Affective modulation of the startle reflex in schizophrenic patients

Abstract: Startle-elicited blinks were measured during the presentation of affective slides in order to investigate emotional responsiveness in 24 male healthy subjects and 34 male schizophrenic patients. Although the two groups did not differ with regard to their subjective and autonomic responses to the slide stimuli, there was a significant difference between the groups in their responses to the startle probes. Patients rated low in affective expression showed a linear response pattern comparable to that of normal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 30 publications
8
49
2
1
Order By: Relevance
“…Modulation of blink responses has proved to be a valuable tool to operationally investigate attentional deficits and information processing dysfunctions in patients with different neuropsychiatric disorders [2,15,[17][18][19]. In general, the acoustic response of the orbicularis oculi muscle is considered to be the most reliable component of the overall startle reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulation of blink responses has proved to be a valuable tool to operationally investigate attentional deficits and information processing dysfunctions in patients with different neuropsychiatric disorders [2,15,[17][18][19]. In general, the acoustic response of the orbicularis oculi muscle is considered to be the most reliable component of the overall startle reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The eyeblink component of the startle response can easily be measured as the EMG activity of the orbicularis oculi muscles using surface electrodes which can be used in investigations of startle excitability under different physiological and pathological conditions. In particular, the assessment of prepulse inhibition of the acoustic startle response represents an operational measure of sensorimotor gating and has become a valuable tool to investigate information processing deficits in various neuropsychiatric disorders [e. g., 1,2,9,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Further, individuals with schizophrenia show intact responses in emotion-modulated startle paradigms during the presentation of pleasant stimuli, when given sufficient time to process the stimuli (Schlenker et al 1995;Curtis et al 1999;Volz et al 2003;Kring et al 2011) and intact memory enhancement for positive stimuli (Mathews and Barch 2004;Horan et al 2006;Hall et al 2007) though see (Herbener et al 2007). …”
Section: Schizophreniamentioning
confidence: 95%
“…90 Evidence for intact affective responses has also been found in emotion-modulated startle, such that individuals with schizophrenia show similar reductions of startle responses when presented with pleasant stimuli and given sufficient time to process the stimuli. 92,97,109 Furthermore, several studies have shown intact memory enhancement for positive stimuli in schizophrenia, 21,110,111 again suggesting intact ''in-the-moment'' response to affect eliciting stimuli (though see Herbener 99 ). Experience sampling studies in schizophrenia find that patients report less intense and less variable positive emotions.…”
Section: Hedonics and Liking In Schizophreniamentioning
confidence: 99%